"Even Though We Have Different Colors, We Are All Equal Here": Immigrants building a sense of community and wellbeing through sport participation. Issue 1 (18th June 2022) - Corvino, Chiara; Martinez‐Damia, Sara; Belluzzi, Mattia; Marzana, Daniela; D'Angelo, Chiara
Abstract: Although there are several studies reporting the beneficial role of sports in immigrant health, more research is needed to understand whether and how these activities can guide the psychological sense of community (SOC) and well‐being outcomes. This study aims at exploring how sport participation among immigrants contributes to developing their SOC and subjective well‐being. We analyzed the experiences of 17 immigrants participating in Balon Mundial (BM), an annual multicultural football tournament in Turin (Italy). A thematic deductive theory‐driven analysis was implemented based on in‐depth interviews. BM developed a psychological SOC by providing immigrants with a safe space—based on norms of accessibility and fair play—to mutually share traditions while forming positive and trusting bonds. All these dimensions of the tournament were connected to an enhancement of immigrants' subjective well‐being in terms of happiness, self‐care, sense of acceptance and cultural intelligence. Sport participation can sustain immigrants' psychological SOC and subjective well‐being under specific conditions: (a) when norms are developed based on inclusion; and (b) when a shared goal and history are built among participants.